THERMAL PERFORMANCE OF HOUSING FOR CALVES COVERED WITH ASBESTOS-FREE FIBER-CEMENT CORRUGATED SHEETS AND AGRO-PRODUCTS ECOLOGICAL LINING ASSOCIATED WITH INSULATING MATERIALS - Barbirato, G.; Fiorelli, J.; Lino, G.; Cravo, J. C. M.; Bertolini, M. S.; Lahr, F. A. R. (Revista Brasileira de Engenharia de Biossistemas, 2015)
This paper describes a study on the potential use of an ecological lining the base particles of the wood processing and agribusiness cane sugar (shavings of Pinus sp. And pomace Saccharum officinarum L.) associated with polystyrene plates expanded (Styrofoam®) and PU-castor, when applied in housing for calves covered with cement tile. For the study, the internal temperature was measured, relative humidity and the temperature and humidity index (ITU) in the summer period, for a period of 21 days. The results indicated that the ITU and internal ambient temperature of the premises with ecological lining associated with Styrofoam® boards and castor oil polyurethane (PU-castor) were lower than those measured in housing for calves unlined were. The images captured by thermographic camera indicate that there was a reduction in the temperature of the inner surface of individual house for calves with lining. The thermographic images captured by camera indicate that the materials used as cushioned liner heat transfer and radiation to the interior of the hutch housing, resulting in lower internal temperatures in these environments.